2015
DOI: 10.1016/j.ascom.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

VIDE: The Void IDentification and Examination toolkit

Abstract: We present vide, the Void IDentification and Examination toolkit, an open-source Python/C++ code for finding cosmic voids in galaxy redshift surveys and N -body simulations, characterizing their properties, and providing a platform for more detailed analysis. At its core, vide uses a substantially enhanced version of zobov (Neyinck 2008) to calculate a Voronoi tessellation for estimating the density field and a performing a watershed transform to construct voids. Additionally, vide provides significant functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
167
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(168 citation statements)
references
References 75 publications
(98 reference statements)
1
167
0
Order By: Relevance
“…Several works have been focusing on measuring the void abundance and its deviation from the expectations of the standard ΛCDM model in the context of various non-standard cosmologies (e.g. [28,82,89,90,95]). In particular, for the case of f (R) gravity, some of these works [82,89,90] have shown that there is an excess of large voids compared to ΛCDM, and that the excess is larger for larger values of the f R0 parameter.…”
Section: Void Abundancesmentioning
confidence: 99%
“…Several works have been focusing on measuring the void abundance and its deviation from the expectations of the standard ΛCDM model in the context of various non-standard cosmologies (e.g. [28,82,89,90,95]). In particular, for the case of f (R) gravity, some of these works [82,89,90] have shown that there is an excess of large voids compared to ΛCDM, and that the excess is larger for larger values of the f R0 parameter.…”
Section: Void Abundancesmentioning
confidence: 99%
“…In fact previous studies of f (R) imprints on void profiles have not investigated the effect of the void finder itself. As we already mentioned void finders such as [37,38] tend to identify voids without ridge for R v ≥ 17Mpc.h −1 (see [65]). Because the fifth force enhances the void ridge, it might be interesting to test the imprint of f (R) for different types of void profiles (for a fixed R v ).…”
Section: Application: Void Profiles Departure From Gr In F (R) Gmentioning
confidence: 99%
“…This last constraint is not mandatory for certain void finders (e.g. [38]), particularly for large voids, and therefore we distinguish this additional condition as a +1 condition.…”
Section: B Density Criteria To Find Voidsmentioning
confidence: 99%
See 2 more Smart Citations